Pengaruh Edukasi Manajemen Diri Terhadap Kepatuhan Mengkonsumsi OAT pada Penderita Tuberkulosis Paru di BLU RSUD Nabire Provinsi Papua - Fendy Yesayas; Risma Yuniarlina; Hary Susilo (FORIKES, 2021)
Self-management education is an educational program that helps improve the compliance of pulmonary TB patients in taking OAT. The purpose of this study was to analyze the effect of self-management education on adherence to consuming OAT in patients with pulmonary TB in BLUD Nabire Regional Hospital, Papua Province. The design used is Pre Experimental with One Group Pre-Post Test Design. Self-management education intervention was given to 106 respondents who were selected by purposive sampling technique. Respondents were given self-management education for 4 weeks, and compliance of consuming OAT was measured using MMAS Questionnaire version 8. Using wilcoxon test, it was declared that there were statistically significant difference in knowledge before and after selfmanagement education (P value = 0.000), there were signifanct difference in family support (P value = 0.000), the role of PMO value of (P = 0.000) and compliance to consume OAT before and after self-management education with a value of (P = 0.000). The results of the ordinal logistic regression test declared a partial effect on the role of PMO and self-management education on OAT consumption compliance P> 0.05 and there is a simultaneous influence on self-management education, age, education level, role of PMO, and family support for compliance consuming OAT (P = 0.305). Researcher recommends the application of self-management education to be one of the intervention for patients with pulmonary TB in improving adherence to taking OAT.Keywords: self-management education; adherence; anti tuberculosis drugsABSTRAKEdukasi manajemen diri merupakan program edukasi yang membantu meningkatkan kepatuhan penderita TB paru dalam mengkonsumsi obat anti tuberkulosis. Tujuan penelitian ini adalah untuk menganalisis pengaruh edukasi manajemen diri terhadap kepatuhan mengkonsumsi OAT pada penderita tuberkulosis paru di BLUD RSUD Nabire Provinsi Papua. Rancangan yang digunakan adalah Pre Experimental dengan One Group Pre-Post Test Design. Intervensi edukasi manajemen diri diberikan terhadap 106 responden yang dipilih dengan teknik purposive sampling. Responden diberikan edukasi manajemen diri selama 4 minggu dan pengukuran kepatuhan mengkonsumsi OAT Mengunakan Kuisoner MMAS versi 8. Hasil penelitian uji beda mengunakan uji wilcoxon ada perbedaan dukungan keluarga nilai P =0,000, peran PMO nilai P =0,000 dan kepatuhan mengkonsumsi OAT nilai P =0,000 sebelum dan sesudah edukasi manajemen diri dengan. Hasil uji regresi logistic ordinal ada pengaruh secara parsial peran PMO dan edukasi manajemen diri terhadap kepatuhan mengkonsumsi OAT P >0,05 dan ada pengaruh secara simultan edukasi manajemen diri, umur, tingkat pendidikan, peran PMO, dan dukungan keluarga terhadap kepatuhan mengkonsumsi OAT p=0,305. Peneliti merekomendasikan penerapan edukasi manajemen diri untuk menjadi salah satu intervensi pada pasien TB paru dalam meningkatkan kepatuhan mengkonsumsi OAT.Kata kunci: edukasi manajemen diri; kepatuhan; obat anti tuberkulosis